2008
DOI: 10.1136/gut.2007.144584
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of extrahepatic vasodilation in portal hypertension

Abstract: In liver cirrhosis, abnormal persistent extrahepatic vasodilation leads to hyperdynamic circulatory dysfunction which essentially contributes to portal hypertension. Since portal hypertension is a major factor in the development of complications in cirrhosis, the mechanisms underlying this vasodilation are of paramount interest. Extensive studies performed in cirrhotic patients and animals revealed that this vasodilation is associated on the one hand with enhanced formation of vasodilators, and on the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(181 citation statements)
references
References 159 publications
(180 reference statements)
6
164
1
10
Order By: Relevance
“…Splanchnic vascular resistance was significantly decreased in weekly embolized rats compared to rats with only a single embolization (Fig 3e). This is in line with hemodynamic findings in portal hypertension [16,25]. There were no significant differences in the MAP (weekly embolization: 87.0 ± 13.2; single embolization: 96.2 ± 12.2; control: 91.0 ± 6.9) and in the cardiac output (weekly embolization: 19.0 ± 1.6; single embolization: 29.8 ± 5.3; control: 16.7 ± 4.1), respectively.…”
Section: Development Of Portal Hypertension In Nciph Ratssupporting
confidence: 74%
“…Splanchnic vascular resistance was significantly decreased in weekly embolized rats compared to rats with only a single embolization (Fig 3e). This is in line with hemodynamic findings in portal hypertension [16,25]. There were no significant differences in the MAP (weekly embolization: 87.0 ± 13.2; single embolization: 96.2 ± 12.2; control: 91.0 ± 6.9) and in the cardiac output (weekly embolization: 19.0 ± 1.6; single embolization: 29.8 ± 5.3; control: 16.7 ± 4.1), respectively.…”
Section: Development Of Portal Hypertension In Nciph Ratssupporting
confidence: 74%
“…Another mechanism seems to be defective contractile signaling in smooth muscle cells in response to vasoconstrictor stimulation [Hennenberg et al 2008]. In addition to the liver itself, little is known about the factors responsible for these defects.…”
Section: Diagnosis Definitionmentioning
confidence: 99%
“…A large number of studies on isolated perfusated mesenteric arteries and aorta of rats with various models of portal hypertension showed that decreased vasoconstrictor response to α 1 -adrenoceptors agonists (phenylephrine, metoksamin, norepinephrine), angiotensin II and vasopressin which persisted even after the removal of endothelium or pharmacological inhibition of endogenous NO production [50]. This hypocontractility can be due to malfunctioning vascular RhoA/Rho kinase signalling or disrupted response to angiotensin II as a result of increased expression of the receptor to G protein-bound protein kinase 2 and protein β-arestyne 2 bound to angiotensin II receptor type 1 [51,52].…”
Section: Carbon Monoxide and Hydrogen Sulfide Mediated Vasodilationmentioning
confidence: 99%